Live-cell protein labelling with nanometre precision by cell squeezing - Alina Kollmannsperger (Nature Portfolio, 2016)
The direct observation of intracellular processes through microscopy can provide key insight into biological pathways. Here the authors demonstrate the combination of microfluidic cell squeezing and fluorescent label delivery to native proteins for high throughput live cell super-resolution imaging.